Improving the performance of finite element simulations on the wheel–rail interaction by using a coupling strategy. (July 2018) - Ma, Yuewei; Markine, Valeri L; Mashal, Abdul Ahad; Ren, Mingfa
Over the past few years, a number of implicit/explicit finite element models have been introduced for the purpose of tackling the problems of wheel–rail interaction. Yet, most of those finite element models encounter common numerical difficulties. For instance, initial gaps/penetrations between two contact bodies, which easily occur when realistic wheel–rail profiles are accounted for, would trigger the problems of divergence in implicit finite element simulations. Also, redundant, insufficient or mismatched mesh refinements in the vicinity of areas in contact can lead to either prohibitive calculation expenses or inaccurate implicit/explicit finite element solutions. To address the abovementioned problems and to improve the performance of finite element simulations, a novel modelling strategy has been proposed. In this strategy, the three-dimensional explicit finite element analysis is seamlessly coupled with the two-dimensional geometrical contact analysis. The contact properties in the three-dimensional finite element analyses, such as the initial "Just-in-contact" point, the exact wheel local rolling radius, etc., which are usually a priori unknown, are determined using the two-dimensional geometrical contact model. As part of the coupling strategy, a technique has been developed for adaptive mesh refinement. The mesh and mesh density of wheel–rail finite element models change adaptively depending on the exact location of the contact areas and the local geometry of contact bodies. By this means, a good balance between the calculation efficiency and accuracy can be achieved. Last, but not least, the advantage of the coupling strategy has been demonstrated in studies on the relationship between the initial slips and the steady frictional rolling state. Finally, the results of the simulations are presented and discussed.